Boosting Health Workforce Performance: A Cross-disciplinary Strategies for juggling Medical Services in Hospital Administration, Health Assistance, General Medicine, Optics, Emergency Medical Services, Laboratory, Pharmacy, and Public Health - Aldilami, Mansour Jamel; Binmadhi, Fahad Abdullah Saad; Alqahtani, Abdulsalam Abdullah; Alqahtani, Abdullah Mohammed Saeed; Alotibi, Fayez Abdullah Fayez; Alsalawi, Ahmed Abdullah; Aljohaani, Abduaziz Muatd Jaber; Brashi, Walaa Mohammed; S. Aljuhani, Mohammed Ahmed; Alzahrani, Meshari Mohammed Saadi (Journal of Ecohumanism, 2024)
The performance of healthcare workers is a critical factor in ensuring high-quality healthcare delivery, particularly in complex and dynamic environments like hospitals and public health settings. This review aims to explore cross-disciplinary strategies to enhance the performance of healthcare professionals across diverse sectors, including hospital administration, general medicine, emergency medical services (EMS), laboratory services, optics, pharmacy, and public health. Key strategies examined include leadership models that foster a supportive work environment, targeted workforce training that adapts to technological advancements, and the promotion of inter-professional collaboration. Additionally, the review addresses the importance of mental health and wellbeing initiatives, which are often overlooked but essential for sustaining worker performance. By synthesizing research from healthcare management, clinical practice, and organizational behavior, the article provides insights on how to build a resilient, motivated, and efficient healthcare workforce capable of responding effectively to evolving healthcare demands.